A new approach to prepare N-/S-doped free-standing graphene oxides for vanadium redox flow battery - Ersozoglu, Mehmet Giray; Gursu, Hurmus; Gencten, Metin; Sarac, Abdulkadir Sezai; Sahin, Yucel (WILEY, 2022)
Nitrogen and sulfur heteroatom-doped graphene oxide (GO) electrodes were produced with a fast, eco-friendly, and, more significantly, functional group-controlled technique, chronoamperometry. N-doped GOs (N-GOs) and S-doped GOs (S-GOs) as binder-free positive electrodes were designed to boost the performance of vanadium redox flow battery as the positive electrodes. The prepared as positive electrode materials for vanadium redox battery were characterized with cyclic voltammetry, Raman spectroscopy, X-ray photoelectron spectroscopy, scanning electron microscopy, and energy-dispersive X-ray spectroscopy. The electrochemical performance of the prepared GO electrodes was investigated through cyclic voltammetry and electrochemical impedance spectroscopy. While S-GOs containing S, and O-containing functional groups were shown high electrical conductivity and stability, N-GOs, containing N and O-containing functional groups were slightly lower electrochemical performance. Among the high-performance electrodes, the S-GO21 synthesized by applying +2.1 V constant potential via the chronoamperometry method exhibited the best performance as the positive electrode for vanadium redox battery. This electrochemical activity result can be correlated to the more S- and O-containing functional groups on the surface of GO.
Keywords: chronoamperometry; N-doped graphene oxide; S-doped graphene oxide; positive electrode; vanadium redox flow battery; GRAPHITE ELECTRODE; NITROGEN; REDUCTION; PERFORMANCE; POLYMER; SULFUR; ROUTE; FELT; Energy & Fuels; Nuclear Science & Technology